2022
DOI: 10.3389/fonc.2022.850454
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Burden in Patients With Hepatocellular Carcinoma Undergoing Transarterial Chemoembolization: Head-to-Head Comparison of Current Scoring Systems

Abstract: ObjectivesRecently, several scoring systems for prognosis prediction based on tumor burden have been promoted for patients with hepatocellular carcinoma (HCC) undergoing transarterial chemoembolization (TACE). This multicenter study aimed to perform the first head-to-head comparison of three scoring systems.MethodsWe retrospectively enrolled 849 treatment-naïve patients with HCC undergoing TACE at six tertiary care centers between 2010 and 2020. The tumor burden score (TBS), the Six-and-Twelve score (SAT), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…TBS was defined as the distance from the origin of a Cartesian plane using maximum tumor size as the X-axis and tumor number as the Y-axis (9). As previously reported, TBS is a valuable tool in evaluating prognosis for colorectal liver metastases, HCC, and ICC (13,26,27). The present study assessed the significance of TBS in dictating the prognosis of patients with cHCC-CCA after curative liver resection.…”
Section: Discussionmentioning
confidence: 76%
“…TBS was defined as the distance from the origin of a Cartesian plane using maximum tumor size as the X-axis and tumor number as the Y-axis (9). As previously reported, TBS is a valuable tool in evaluating prognosis for colorectal liver metastases, HCC, and ICC (13,26,27). The present study assessed the significance of TBS in dictating the prognosis of patients with cHCC-CCA after curative liver resection.…”
Section: Discussionmentioning
confidence: 76%
“…Tumor burden, as measured by its largest size and number of tumors, is a common factor that has been incorporated into many HCC prognostic models, similar to our scoring system ( 17 , 28 31 ). Previous studies have shown that tumor burden is significantly associated with the survival rate of HCC patients ( 27 , 32 , 33 ). Unlike liver transplantation criteria ( 28 , 34 ), there was no defined threshold for tumor burden to be an absolute contraindication for TACE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that tumor burden influences the survival and tumor response of patients with HCC. 33 , 34 Hence, BCLC stage A or stage B patients with a single tumor of length ≤5 cm, a single tumor of length >5 cm, or multiple tumors were included for subgroup analysis. The results revealed that the PFS risk in patients subjected to TACE-P-based treatment methods was higher than that in patients subjected to TACE-R-based treatment methods (the results were obtained when patients with a single tumor no more than 5 cm in length (following PSM) were studied).…”
Section: Discussionmentioning
confidence: 99%